Pemerolehan Kalimat Bahasa Minangkabau: Studi Kasus pada Anak Usia Empat Tahun tiga Bulan - Zulhidayanti, Zulhidayanti; Juita, Novia; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was to analyze: (1) the types of sentences that diujarkan by children aged four years and three months, and (2) sentence patterns children aged four years and three months. The theory used is the theory of (1) language acquisition, (2) the child, (3) acquisition of sentence and (4) the sentence pattern. This research is descriptive qualitative research method. This study used data types are derived from verbal utterances children aged four years and three months. Data obtained by using techniques of observation, recording, and interviews. Data obtained through the tape, and then classified by type of sentence, sentence patterns, and forms of utterance based on the purpose of the study, and then formulated into a conclusion.